2019
DOI: 10.1111/bjh.16042
|View full text |Cite
|
Sign up to set email alerts
|

Association of gene mutations with time‐to‐first treatment in 384 treatment‐naive chronic lymphocytic leukaemia patients

Abstract: Summary This study correlated somatic mutation results and known prognostic factors with time‐to‐first treatment (TTFT) in 384 treatment‐naïve (TN) chronic lymphocytic leukaemia (CLL) patients to help determine disease‐specific drivers of early untreated CLL. CLL DNA from either peripheral blood or bone marrow underwent next generation targeted sequencing with a 29‐gene panel. Gene mutation data and concurrent clinical characteristics, such as Rai/Binet stage, fluorescence in situ hybridisation (FISH), ZAP70/C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 49 publications
(98 reference statements)
1
27
0
Order By: Relevance
“…The percentage of del17p cells has an impact on the prognosis of CLL patients, and the low percentage of del17p cells predicts a better TTFT [66]. However, another study revealed that neither del17p, mutated p53, nor complex karyotypes is associated with TTFT, which suggests that they have limited roles in early CLL patients but may take effect in relapsed disease [47]. Besides chromosome aberrations above, del6q, del9p21, del10q23, total or partial trisomies of chromosomes 3, 8, 18, 19, and duplications in 2p24 also have an impact on prognosis in CLL [67].…”
Section: Chromosome Aberrationsmentioning
confidence: 99%
“…The percentage of del17p cells has an impact on the prognosis of CLL patients, and the low percentage of del17p cells predicts a better TTFT [66]. However, another study revealed that neither del17p, mutated p53, nor complex karyotypes is associated with TTFT, which suggests that they have limited roles in early CLL patients but may take effect in relapsed disease [47]. Besides chromosome aberrations above, del6q, del9p21, del10q23, total or partial trisomies of chromosomes 3, 8, 18, 19, and duplications in 2p24 also have an impact on prognosis in CLL [67].…”
Section: Chromosome Aberrationsmentioning
confidence: 99%
“…In addition, by taking advantage of the genetic heterogeneity of CLL, mutations of genes involved in CLL pathogenesis have been tested as biomarkers for identifying early stage CLL patients with a higher risk of progression and treatment requirement. These studies point to mutations of SF3B1, NOTCH1, ATM, U1, and XPO1 as molecular predictors of shorter TTFT [7,56,57]. Interestingly, TP53 disruption is not associated with a shorter TTFT, in line with the notion that TP53 disruption interacts with treatment with chemotherapeutic agents, but not with a watch and wait strategy that does not expose CLL cells carrying TP53 disruption to the positive selection pressure exerted by ineffective chemotherapy [55,56].…”
Section: Management Of Asymptomatic Cll Patientsmentioning
confidence: 70%
“…Recent studies have tried to identify the clinical and molecular features of early stage CLL patients managed with a watch and wait approach and who might manifest treatment requirement soon after diagnosis [6,[55][56][57][58]. The pattern of tumor growth of untreated CLL has been investigated by analyzing serial longitudinal samples collected between diagnosis and the time of treatment requirement [6].…”
Section: Management Of Asymptomatic Cll Patientsmentioning
confidence: 99%
See 1 more Smart Citation
“…An important question is how can this be added to by the more recent identification of recurrent genetic mutations in CLL. In the current paper, (Hu et al , ) the authors studied the impact on time from diagnosis to time to first treatment (TTFT) of detection of mutations in a 29 gene panel and looked for associations with a variety of standard prognostic factors in a cohort of 384 treatment naïve CLL. They demonstrate that mutated ATM ( P < 0·001), NOTCH1 ( P < 0·001) and SF3B1 ( P = 0·002) as well as unmutated IGHV ( P < 0·001), del(11q) ( P < 0·001) and trisomy 12 ( P < 0·001) by hierarchal FISH and advanced Rai ( P = 0·05) and Binet ( P < 0·001) stages were associated with shorter TTFT.…”
mentioning
confidence: 99%